Tumor-microenvironment-activatable polymer nano-immunomodulator for precision cancer photoimmunotherapy - Liu, Jing (2022)
Cancer nanomedicine combined with immunotherapy has become a promising strategy for treating cancer in terms of safety and potency; however, precise regulation of the activation of antitumor immunity remains challenging. Herein, a smart semiconducting polymer nano-immunomodulator (SPNI), which responds to the acidic tumor microenvironment (TME), for precision photodynamic immunotherapy of cancer, is reported. The SPNI is self-assembled by a near-infrared (NIR)-absorbing semiconducting polymer and an amphipathic polymer conjugated with a Toll-like receptor 7 (TLR7) agonist via an acid-labile linker. Upon arrival at tumor site, SPNI undergoes hydrolysis and triggers an efficient liberation of TLR7 agonist in response to the acidic TME for dendritic cell activation. Moreover, SPNI exerts photodynamic effects for direct tumor eradication and immunogenic cancer cell death under NIR photoirradiation. The synergistic action of released immunogenic factors and acidic-TME-activated TLR7 agonist can serve as an in situ generated cancer vaccine to evoke strong antitumor activities. Notably, such localized immune activation boosts systemic antitumor immune responses, resulting in enhanced cytotoxic CD8+ T infiltration to inhibit tumor growth and metastasis. Thereby, this work presents a general strategy to devise prodrug of immunotherapeutics for precise regulation of cancer immunotherapy.